FRAMING THE FLAMES: analyzing news coverage of the 2019 Amazon rainforest fires by Brazilian and American newspapers - Pires Andrus, Leticia; Waters, Stephenson (Brazilian journalism research, 2025)
ABSTRACT – The purpose of this research was to analyze how major American and Brazilian newspapers framed the Amazon rainforest fire that occurred in August 2019. Framing theory was used as the foundation to build the literature review and guide this study to the research questions and hypotheses. The sample in the analysis was composed of news articles (N = 250) from the American newspapers The New York Times and The Washington Post, and the Brazilian newspapers Folha de S.Paulo and O Estado de S. Paulo. These newspapers were chosen based on their circulation and the influence of these media in their respective countries. The frames were selected using previous literature that analyzed organizational crises and new media coverage of environmental issues. The relevance of this study relies on the environmental and economic importance of the Amazon rainforest territory not only for Brazil but also for other countries around the world. The deforestation and the destruction of this green area impact the population of many countries in South America and represent an environmental crisis. Due to the importance of the Amazon rainforest, this study seeks to understand what message media from different countries are sending to their audience when covering the 2019 fires in the Amazon. This paper contributed to improving the understanding of the application of framing theory in communication research, and the understanding of how the use of distinct media frames by cross-cultural media can imply a particular message to the audience. RESUMO – O objetivo desta pesquisa foi analisar como os principais jornais americanos e brasileiros enquadraram o incêndio na Floresta Amazônica que ocorreu em agosto de 2019. A teoria do enquadramento foi usada como base para construir a revisão da literatura e orientar este estudo para as perguntas e hipóteses da pesquisa. A amostra da análise foi composta de artigos de notícias (N = 250) dos jornais americanos The New York Times e The Washington Post, e dos jornais brasileiros Folha de S.Paulo e O Estado de S. Paulo. Esses jornais foram escolhidos com base em sua circulação e na influência dessa mídia em seus respectivos países. Os quadros foram selecionados com base na literatura anterior que analisou crises organizacionais e a cobertura da nova mídia sobre questões ambientais. A relevância deste estudo se baseia na importância ambiental e econômica do território da Floresta Amazônica não só para o Brasil, mas também para outros países do mundo. O desmatamento e a destruição dessa área verde afetam a população de muitos países da América do Sul e representam uma crise ambiental. Devido à importância da Floresta Amazônica, este estudo procura entender qual mensagem a mídia de diferentes países está enviando ao seu público ao cobrir os incêndios de 2019 na Amazônia. Este artigo contribuiu para melhorar a compreensão da aplicação da teoria de enquadramento na pesquisa de comunicação e a compreensão de como o uso de enquadramentos de mídia distintos pela mídia intercultural pode implicar uma mensagem específica para o público. RESUMEN – El propósito de esta investigación fue analizar cómo los principales periódicos estadounidenses y brasileños enmarcaron el incendio de la selva amazónica que ocurrió en agosto de 2019. La teoría del encuadre se utilizó como base para construir la revisión de la literatura y guiar este estudio hacia las preguntas e hipótesis de investigación. La muestra del análisis se compuso de artículos de noticias (N = 250) de los periódicos estadounidenses The New York Times y The Washington Post, y de los periódicos brasileños Folha de S.Paulo y O Estado de S. Paulo. Estos periódicos se eligieron en función de su tirada y de la influencia de estos medios en sus respectivos países. Los encuadres se seleccionaron a partir de la bibliografía previa que analizaba las crisis organizativas y la cobertura de los nuevos medios de comunicación de las cuestiones medioambientales. La relevancia de este estudio radica en la importancia medioambiental y económica del territorio de la selva amazónica no sólo para Brasil, sino también para otros países del mundo. La deforestación y la destrucción de esta zona verde afectan a la población de muchos países de Sudamérica y representan una crisis medioambiental. Debido a la importancia de la selva amazónica, este estudio busca entender qué mensaje están enviando los medios de comunicación de diferentes países a su audiencia cuando cubren los incendios de 2019 en el Amazonas. Este trabajo contribuyó a mejorar la comprensión de la aplicación de la teoría del encuadre en la investigación de la comunicación, y la comprensión de cómo el uso de distintos encuadres mediáticos por parte de medios transculturales puede implicar un mensaje particular para la audiencia.